Elements of effective teaching from the perspective of anatomist - Saiful Bahri, Talip; Muhamad Saiful Bahri, Yusoff; Zul Izhar, Mohd Ismail; Siti Nurma Hanim, Hadie (2022)
Introduction: Previous evidence shows that effective teaching is highly dependent on the ability of educators in designing lesson plans and implementing engaging teaching strategies that ensures the attainment of learning outcomes. Nevertheless, there is a scarcity of empirical evidence of effective teaching in anatomy education sciences. Hence this study aimed to explore the elements of effective teaching from the perspective of anatomists.